Empirical evidence of e-banking and customer perception on banks service quality in Nigeria - Usman, Umar; Jibril, Abdulsalam (2014)
As competition in the financial services market increases, high street banks are faced with the strategic challenge of more effectively managing customers of varying worth through the delivery platform.The main objective of the study is to find out the relationship between E-banking and customer perception of banks service quality a chi-square was used to run and determine the level of significant relationship between dependent variable and independent variables, while regression analysis is conducted using SPSS to examine how strong the relationship between the dependent variable and independent variables,the findings show a positive relationship between E-banking and customer perception of banks service quality, therefore in line with the findings and conclusions of this study, it is recommended that there is the need to deploy more resources to improve on the existing relationship on the activities between E-banking and customer perception of banks service quality in Nigeria.